The DAR Survey of Physicians' Use of GLP-1 Receptor Agonists and SGLT2 Inhibitors during Ramadan - Hassanein, Mohamed; Afandi, Bachar; Beshyah, Salem A. (Journal of Diabetes and Endocrine Practice, 2025)
While existing studies and guidelines have supported the safety of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter-2 (SGLT2) inhibitors during Ramadan, little is known about how these recommendations are applied by physicians in real-world settings.This survey aimed to evaluate physicians' perceptions, practices, and use of GLP-1 RAs and SGLT2 inhibitors during Ramadan by assessing prescribing patterns, counseling approaches, and risk mitigation strategies.A cross-sectional online survey was conducted in December 2024. The survey was disseminated via targeted e-mails and professional networks, including participants of prior DAR Alliance activities.A total of 939 physicians responded, with the majority from the Middle East and North Africa and South-East Asia regions. Endocrinologists accounted for over 40% of the sample. Most physicians reported treating over 50 patients with type 2 diabetes per month who fast during Ramadan. Endocrinologists were significantly more likely to initiate therapy earlier, adjust doses proactively, and provide structured counseling compared with non-endocrinologists, who exhibited more conservative and variable practices. Timing, dosing, and counseling practices varied, with some divergence between endocrinologists and non-endocrinologists. Nonetheless, both groups adhered to safety-focused strategies, including managing gastrointestinal side effects and reducing the risk of dehydration.Although access to GLP-1 RAs and SGLT2 inhibitors is generally not a barrier, hesitancy persists among physicians in initiating or adjusting these agents during Ramadan. This variation may lead to inconsistent patient care and missed opportunities for optimal metabolic and cardiorenal protection. Clear, evidence-based guidance and structured training initiatives are essential to unify clinical practice and enhance patient safety in this unique setting.
Keywords: Ramadan fasting; type 2 diabetes; GLP-1 RA; SGLT2 inhibitors; hyperglycemia; dehydration; survey